The Cytoskeletal Elements MAP2 and NF-L Show Substantial Alterations in Different Stroke Models While Elevated Serum Levels Highlight Especially MAP2 as a Sensitive Biomarker in Stroke Patients - Bianca Mages; Thomas Fuhs; Susanne Aleithe; Alexandra Blietz; Constance Hobusch; Wolfgang Härtig; Stefan Schob; Martin Krueger; Dominik Michalski (Molecular Neurobiology, 2021)
In the setting of ischemic stroke, the neurofilament subunit NF-L and the microtubule-associated protein MAP2 have proven to be exceptionally ischemia-sensitive elements of the neuronal cytoskeleton. Since alterations of the cytoskeleton have been linked to the transition from reversible to irreversible tissue damage, the present study investigates underlying time- and region-specific alterations of NF-L and MAP2 in different animal models of focal cerebral ischemia. Although NF-L is increasingly established as a clinical stroke biomarker, MAP2 serum measurements after stroke are still lacking. Therefore, the present study further compares serum levels of MAP2 with NF-L in stroke patients. In the applied animal models, MAP2-related immunofluorescence intensities were decreased in ischemic areas, whereas the abundance of NF-L degradation products accounted for an increase of NF-L-related immunofluorescence intensity. Accordingly, Western blot analyses of ischemic areas revealed decreased protein levels of both MAP2 and NF-L. The cytoskeletal alterations are further reflected at an ultrastructural level as indicated by a significant reduction of detectable neurofilaments in cortical axons of ischemia-affected areas. Moreover, atomic force microscopy measurements confirmed altered mechanical properties as indicated by a decreased elastic strength in ischemia-affected tissue. In addition to the results from the animal models, stroke patients exhibited significantly elevated serum levels of MAP2, which increased with infarct size, whereas serum levels of NF-L did not differ significantly. Thus, MAP2 appears to be a more sensitive stroke biomarker than NF-L, especially for early neuronal damage. This perspective is strengthened by the results from the animal models, showing MAP2-related alterations at earlier time points compared to NF-L. The profound ischemia-induced alterations further qualify both cytoskeletal elements as promising targets for neuroprotective therapies.

Transcriptional Response and Morphological Features of the Neurovascular Unit and Associated Extracellular Matrix After Experimental Stroke in Mice - Susanne Aleithe; Alexandra Blietz; Bianca Mages; Constance Hobusch; Wolfgang Härtig; Dominik Michalski (Molecular Neurobiology, 2019)

RNAi in murine hepatocytes: the agony of choice—a study of the influence of lipid-based transfection reagents on hepatocyte metabolism - Jan Böttger; Katrin Arnold; Carlo Thiel; Christiane Rennert; Susanne Aleithe; Ute Hofmann; Sebastian Vlaic; Susanne Sales; Andrej Shevchenko; Madlen Matz-Soja (Archives of Toxicology, 2015)